“My Role Is Important, but Not Critical”: Why Intention Matters in the Creation of Victim Assistance Units in Israel - Gesser, Nili (Victims & offenders, 2022)
Crime victims often need assistance navigating the unfamiliar legal system. Limited research exists, however, on those tasked with helping victims, the victim assistance units (VAUs), particularly outside the US. Indeed, there have been calls in the literature for more comparative research in this area. Responding to their call, this exploratory study analyzes the creation of VAUs within the district attorney’s offices (DAO) in Israel following specific victims’ rights legislation. Using qualitative interviews with representatives from three quarters of the VAUs in Israel (N = 6), the paper explores the formation of two models of VAUs, examines the specific location of the VAU within the DAOs, and analyzes various influences on the work of the VAU. I argue that limited resources, cultural organization and professional ethos prevent VAUs from fully addressing victims’ needs. In order to best respond to victims’ needs, the VAUs should expand their contact with victims and receive sufficient resources to do so. The Israeli case study demonstrates that to best assist victims, VAUs should be created with a “victim-centered” agenda. This study advances our knowledge of victim workers outside the US, highlighting the impact of their DAO’s affiliation and its potential impact on victims.